Hsp65-Producing Lactococcocus lactis Prevents Antigen-Induced Arthritis in Mice - Gusmao-Silva, Guilherme; Aguiar, Sarah Leão Fiorini; Miranda, Mariana Camila Gonçalves; Guimarães, Mauro Andrade; Alves, Juliana Lima; Vieira, Angélica Thomaz; Cara, Denise Carmona; Miyoshi, Anderson; Azevedo, Vasco Ariston; Oliveira, Rafael Pires; Faria, Ana Maria Caetano (Frontiers in Immunology, 2020)
Oral tolerance is the physiological process that enables the immune system to differentiate between harmless dietary and microbiota antigens from pathogen-derived antigens. It develops at the mucosal surfaces and can result in local and systemic regulatory and anti-inflammatory effects. Translation of these benefits to the clinical practice faces limitations involving specificity and doses of antigen and regimens of feeding posing caveats to the therapeutic use of oral tolerance. To circumvent these problems, we developed a recombinant Hsp65 delivered by the acid lactic bacteria Lactococcus lactis NCDO 2118. Hsp65 is a ubiquitous protein overexpressed in inflamed tissues and capable of inducing immunoregulatory mechanisms. L. lactis has probiotic properties and is commonly and safely used in dairy products. In this study, we showed that continuous delivery of HSP65 in the gut mucosa by L. lactis is a potent tolerogenic stimuli inducing regulatory CD4+LAP+ T cells that prevented collagen-induced and mBSA-induced arthritis in mice. Clinical and histological signs of arthritis were inhibited as well as levels of inflammatory cytokines such as IL-17 and IFN-gamma, serum titers of anti-collagen antibodies and rheumatoid factor. Oral administration of L. lactis induced alterations in microbiota composition towards an increased abundance of anaerobic bacteria such as Bifidobacterium and Lactobacillus. Tolerance induction to HSP65 by the recombinant L. lactis was associated with increase in IL-10 production by B cells and it was dependent on LAP+ T cells and TLR2 signaling. Therefore, HSP65-producing treatment induced effective tolerance and prevented arthritis development suggesting it can be used as a therapeutic tool for autoimmune diseases.